The Effect of System Quality and Information Quality on the Effectiveness of Tax Reporting through Coretax - Olivia Sindi Sapan; Tantik Sumarlin; Eka Satria Wibawa (Universitas Sains dan Teknologi Komputer, 2026)
Digital transformation in tax administration through the implementation of Coretax requires high system quality and information quality to improve the effectiveness of tax reporting. This study aims to analyze the effects of system quality and information quality on the effectiveness of tax reporting through Coretax. A quantitative explanatory approach was employed using survey data from 70 individual taxpayers in Semarang Regency. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both system quality and information quality have positive and significant effects on tax reporting effectiveness. System quality has a stronger influence than information quality, indicating that ease of use, reliability, response speed, and system integration are essential for effective tax reporting. The model explains 53.9% of the variance in tax reporting effectiveness, indicating moderate explanatory power. These findings support the DeLone and McLean Information Systems Success Model and suggest that improving both system quality and information quality can enhance the effectiveness of digital tax reporting through Coretax. Future studies are recommended to involve larger samples and broader research areas to improve the generalizability of the findings.